2014
DOI: 10.5137/1019-5149.jtn.10153-13.1
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic transaqueductal removal of fourth ventricular neurocysticercosis: report of three cases

Abstract: In this study, we try to present our experience of transaqueductal removal of the fourth ventricular neurocysticercosis (FVNCC) with a flexible neuroendoscope. Three cases of the fourth ventricular cysticercosis were transaqueductally removed with FUJINON EB-270P flexible neuroendoscope through a frontal precoronal burr hole. The diagnosis was established on imaging and confirmed on histology in all of the cases. Complete excision of cysts in the fourth ventricle was performed in all cases with no significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…We also conducted a literature review looking for reported cases with surgical/ histopathological confirmation of ventricular cysticercosis during the past 20 years. A total of 21 papers describing 29 patients, where case descriptions and neuroimaging findings were appropriately detailed as to apply our set to diagnostic criteria, were found [35,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Despite the fact that most of these patients did not had a serum EITB performed, the set allowed a definitive pre-operative diagnosis of NCC in 23 cases (one absolute criterion in 12, two major neuroimaging in six, and one major neuroimaging plus one confirmative in five), and a probable diagnosis in the remaining six patients.…”
Section: Additional Evaluationsmentioning
confidence: 99%
“…We also conducted a literature review looking for reported cases with surgical/ histopathological confirmation of ventricular cysticercosis during the past 20 years. A total of 21 papers describing 29 patients, where case descriptions and neuroimaging findings were appropriately detailed as to apply our set to diagnostic criteria, were found [35,37,[56][57][58][59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74]. Despite the fact that most of these patients did not had a serum EITB performed, the set allowed a definitive pre-operative diagnosis of NCC in 23 cases (one absolute criterion in 12, two major neuroimaging in six, and one major neuroimaging plus one confirmative in five), and a probable diagnosis in the remaining six patients.…”
Section: Additional Evaluationsmentioning
confidence: 99%